Application of response surface methodology and central composite rotatable design (CCDR) for modelling the influence of agro-industrial waste in lactic acid biosynthesis - Jaqueline Boldt Capellari; Eduarda Zeni Neves; Ana Paula Testa Pezzin; Michele Cristina Formolo Garcia; Giannini Pasiznick Apati; Andrea Lima dos Santos Schneider (Acta Biológica Catarinense, 2020)
Lactic acid (LA) is one of the most important organic acids, with a wide range of industrial and biotechnological applications and can be produced by chemical synthesis and microbial culture. However, the biotech pathway is generally preferred because it provides an optically pure product. In this context, the purpose of this work was to evaluate LA biosynthesis by Lactobacillus amylovorus using molasses as carbon source (CS) and corn steep liquor as nitrogen source (NS) in a central composite rotatable design (CCRD) varying the concentration CS and NS, as well as to validate the model. The method for microbial culture followed an experimental design of the CCRD type, conducted without agitation, at 37ºC in Erlenmeyer flask, with pH in spontaneous evolution. The results showed that, using molasses and corn steep liquor as alternative sources, LA production ranged from 2.8 to 4.6 g/L, respectively, with the most favourable condition being 40.0 g of molasses and 250 g of corn steep liquor. It was possible, from the experimental design, to ascertain the selection of the best conditions for the microbial culture, demonstrating the feasibility of replacing CS and NS by agro-industrial waste, thus reducing the cost of producing LA.